Effect of non-genetic factors on production performance of Mehsana buffalo at organized farm - Rimee Dhakad, A. P. Chaudhary, J. P. Gupta and Sadhana Tiwari (Indian Journal of Dairy Science, 2024)
The present investigation included the data pertaining to lactation records of 301 Mehsana buffaloes, spread over a period of 30 years (1991-2020), collected from the records maintained at Livestock Research Station, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, District Banaskantha, Gujarat; to know the effects of non-genetic factors on the production performance of Mehsana buffaloes.  The data pertaining to different performance traits was collected from the records of the farm and analysed to know the effects of non-genetic factors like- period of calving, season of calving, parity and age at first calving group on the performance traits. The overall LSM of 305-DMY, TMY and LL was observed 1714.75 ± 27.30 lit (N=1171), 1765.55 ± 28.61 lit (N=1186) and 273.28 ± 3.66 days (N=1164), respectively. The effects of period of calving (P≤0.05), season of calving (P≤0.01) and parity (P≤0.01) was significant on 305-DMY, but TMY was affected by period of calving, season of calving and AFC group (P≤0.01). Similarly, LL was significantly (P≤0.05) influenced by the period of calving and AFC group, but season of calving and parity had highly significant (P≤0.01) effect on LL of Mehsana buffaloes. Therefore, b ased on these observations it was concluded that significant effect of non-genetic factors play an important  role to improve the production performance of the Mehsana buffalo herd, therefore emphasis must be give n on nutrition, management and health cover practices to improve the performance of the indigenous breed on the farm.